Ortographic and Morphological Problems in Headword Identification, Selection and Presentation in ALLEX - Chimhundu, Herbert (Lexikos, 1994)
This article discusses aspects of an on-going lexical computing project at the University of Zimbabwe, known as ALLEX, the acronym for African Languages Lexical Project. ALLEX is a collaborative, multi-faceted, long-term, computer-aided lexicography project that is intended to produce a series of dictionaries, glossaries and other language reference works in the indigenous languages of Zimbabwe, starting with the first ever monolingual Shona dictionary, which is already at an advanced stage of preparation, and which will also be the first corpus-based dictionary in Zimbabwe. The article confines itself to problems relating to word formation processes in Shona, specifically with reference to the lexicographers' need to ensure consistency in (i) identifying word forms as headwords in the running texts of the corpus, (ii) selecting from among these headwords to decide which ones to enter in the dictionary, and (iii) presenting the entries in the standard orthography. First, an outline is given of the project's background, objectives, priorities, guidelines and work in progress. The article then focuses on specific problems encountered, and discusses these, and some of the solutions, in the light of advances in computer lexicography, with particular reference to concordancing. It will become evident that the problems encountered by the ALLEX Team have to do with the unlimited capacity of the Shona language's basic and derivational word formation processes, which it shares with the other languages in the Bantu family. Therefore, it will be suggested that these problems, and the solutions that are being worked out, have much wider implications that go beyond Shona and Zimbabwe.